The Effect of Different Types of Bait on the Main Catch of Mud Crabs (Scylla serrata) Using Pento Fishing Gear in the Kerandin River, Lingga Regency, Riau Islands Province - Novelia Shafyra; Jonny Zain; Nofrizal Nofrizal (Tropical Marine Environmental Sciences, 2026)
The Kerandin River is located in North Lingga District, Lingga Regency, one of the districts in the Riau Islands Province. Geographically, Lingga Regency is situated between 0°20' N and 0°40' S and 103°30' E and 105°00' E. The residents of Kerandin Village earn their livelihood as farmers and fishermen. One of these potentials is the potential for fisheries, including both capture fisheries and aquaculture. The primary fishery commodity in Lingga Regency is the Mangrove Crab (Scylla serrata). Mangrove crabs are a fishery product with significant economic value, typically caught using pento fishing gear. Pento is a static fishing tool that requires bait to operate. People in Kerandin Village use stingrays as bait. However, one potential bait in the Kerandin River is cheap and easy to obtain but has not been used as bait, namely mullet, which will be tested as an alternative bait for catching mangrove crabs. This research used the Experimental Fishing method, and the data were analyzed using normality tests and T-tests. The research showed that the bait for belukang (Hexanematichthys sagor) produced more crab catches than the bait for stingrays (Trygon sephen). The T-test comparing these two bait types revealed a significant difference, with a value of -2.804 (df = 18) and a significance level of 0.006.